Pengaruh Kualitas Pelayanan Petugas AVSEC terhadap Kepuasan Staf di Security Check Point Bandara Internasional Juanda Sidoarjo - Rahman, Fiqri Maulana; Tamara, Amelia Puspa (Jurnal Manajemen Dirgantara, 2024)
Miscommunication between Aviation Security officers and tenant officers and airline officers at the security check point of Juanda International Airport, Sidoarjo often occurs due to the poor quality of information provided by fellow Aviation Security officers at SCP-1. As a result, officer activities are hampered. This affects staff satisfaction. On this basis, the researcher conducted a study to determine the effect of service quality on staff satisfaction. This study was conducted using a quantitative method where primary data collection was obtained by distributing questionnaires to 100 respondents. Sampling was carried out using the non-probability sampling method. The collected data were then analyzed using simple linear regression, partial test (T test), and coefficient of determination. The results showed that service quality had a significant effect on staff satisfaction at Juanda International Airport, Sidoarjo. This is evident from the statistical analysis carried out, where the calculated t value (9.087) far exceeded the t table value (1.994), with a significance level of 0.00 which is smaller than 0.05. Thus, it can be concluded that the Ha hypothesis in this study can be accepted. In addition, the results of the T-test calculation show that the service quality variable has an influence of 54.8% on the level of staff satisfaction.